Comparative Study of Sampling Technique, Surface Type, and DNA Quantity in Touch DNA: A Systematic Review - Mawaddani, Nala (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Touch DNA analysis has become increasingly important in forensic investigations. This systematic review aims to compare the effectiveness of various sampling techniques on different surface types and examine the concentration of DNA obtained. Following PRISMA guidelines, relevant studies were identified through PubMed, Scopus, and Web of Science databases. Data were extracted using NVivo and synthesized using a narrative approach, while study quality was assessed using the Mixed Methods Appraisal Tool (MMAT). Swabbing, particularly double swabbing, was the most common technique. However, tape lifting was more effective on porous/uneven surfaces, and wet-vacuum sampling outperformed double swabbing on brick. DNA concentrations varied (0.002−0.707 ng/μL) based on surface type and sampling method. Findings provide guidance for forensic practitioners in selecting optimal sampling techniques, refining DNA extraction protocols, and interpreting results. Nevertheless, methodological heterogeneity and laboratory focus limit generalizability. This review offers a comprehensive understanding of factors influencing touch DNA analysis success. Future research should focus on larger, standardized studies, novel sampling techniques, and advanced DNA analysis methods to address challenges associated with degraded or limited touch DNA samples. Continued research is crucial for enhancing the reliability and applicability of touch DNA evidence in forensic investigations.